Sejarah Zaman Darurat 1948-1960 : Kajian Bibliografi Beranotasi - Tiew, W.S. (Persatuan Muzium Malaysia, 2004)
List a collection of 97 resources on the history of Emergency in Malaya 1948-1960 available in the Main Library of Universiti Malaya.